Pathophysiology and Treatment of Malignant Hyperthermia. (April 2021) - Gregory, Haili; Weant, Kyle A.
Abstract : Malignant hyperthermia (MH) is caused by a genetic disorder of the skeletal muscle that induces a hypermetabolic response when patients are exposed to a triggering agent such as volatile inhaled anesthetics or depolarizing neuromuscular blockers. Symptoms of MH include increased carbon dioxide production, hyperthermia, muscle rigidity, tachypnea, tachycardia, acidosis, hyperkalemia, and rhabdomyolysis. Common scenarios for triggering agents are those used are during surgery and rapid sequence intubation. Hypermetabolic symptoms have a rapid onset; hence, prompt recognition and treatment are vital to prevent morbidity and mortality. The first-line treatment agent for an MH response is dantrolene. Further treatment includes managing complications related to a hypermetabolic response such as hyperkalemia and arrhythmias. This review is focused on the recognition and treatment considerations of MH in the emergency department to optimize therapy and improve patient morbidity and mortality.